PENGUATAN PENTINGNYA MEMBACA MELALUI PROGRAM LITERASI PADA WARGA BINAAN LAPAS KELAS II A KOTA BAUBAU - Safaruddin Yahya; Kadar Risman; Nurmin Aminu (Gapenas Publisher, 2023)
The purpose of community service activities at the Class II A prison in Baubau City is to provide strengthening training on the importance of reading as a basis for information and knowledge in determining attitudes. Reading is basically a process of reasoning and finding ideas that can be used in doing and choosing good actions. Literacy activities are very important for the formation of perspectives and awareness to distinguish good and bad values. In this service, the method used is the provision of material with a lecture approach followed by training in binding meaning, conveying and writing it down in personal notes. This activity is able to improve the reading and writing skills of the inmates as well as provide positive benefits for the inmates to reflect on themselves through reading motivational books to realize an intellectual and noble personality